Role of cerium-doping in CoFe2O4 electrodes for high performance supercapacitors. (June 2020) - Nabi, Ghulam; Raza, Waseem; Kamran, Muhammad Arshad; Alharbi, Thamer; Rafique, Muhammad; Tahir, Muhammad Bilal; Hussain, Sajad; Khalid, N.R.; ul-Aain, Qurat; Malik, Nafisa; Ahmed, Rashid S.; Cao, CB
Highlights: Cerium doping role in CoFe2 O4 nanostructure for high performance supercapacitor application. Higher ionic radius of Ce 3+ formed the local distortion in the crystal lattice of CoFe2 O4 which play crucial role in the enhancement of specific capacitance. The excellent specific capacitance have been obtained with Ce0.5 Co2 Fe1.5 O4 which is 937.50 Fg −1 Cycling life stability is 82.3% after 4000 cycles which is reasonable. Abstract: Cerium-doped cobalt spinel ferrite {Cex Co2 Fe2-x O4 (x = 0, 0.3, 0.5)} electrode nanomaterials have been synthesized for the first time. The role of Ce doping for the enhancement of the performance of the supercapacitor has been discussed briefly. SEM analysis showed the almost spherical grain nanoparticles in the range of 40-220 nm with non-uniform cluster and large agglomeration. EDX analysis represented the chemical composition of pure and cerium-doped spinel cobalt ferrite nanomaterials. In PL studies the predominant UV/visible, violet, and blue emission have been observed which are crucial for LEDs. The electrochemical studies of Cex CoFe2-x O4 (x = 0, 0.3, 0.5) electrodes were investigated by using CV, GCD and EIS in 1 M KOH electrolyte solution. The highest specific capacitance (937.50 Fg −1 ) have been obtained with long cycling life 82.3% retention after 4000 th cycles. Hence, the fabricated Ce0.5 CoFe1.5 O4 electrode is a favorable candidate for super-capacitor applications.